Analysis of Factors Affecting the Satisfaction of Associate Degree Students with The Flipped Classroom - Guo, Qian; Wang, Ruijue (Scholar: Human Sciences, 2024)
Purpose: Flipped classroom is an educational approach that reverses the traditional model of classroom instruction, and is reserved for class discussion and interactive projects. This research paper investigates the key factors that significantly impact the use of flipped classrooms at the associate degree level at the Chengdu Vocational University of Art. The framework proposes causal relationships between knowledge, skills, task orientation, behavioral engagement, active learning, and satisfaction. Research design, data, and methodology: Researchers distributed questionnaires to 500 associate degree students who had experienced flipped classroom learning using various sampling methods. Data analysis was conducted using structural equation modeling (SEM) and confirmatory factor analysis (CFA), including model fit, reliability, and validity. Results: Results indicate that active learning significantly affects satisfaction, behavioral engagement has a significant impact on active learning, and knowledge, skills, and active learning have a significant impact on satisfaction. Task Orientation does not have a significant impact on satisfaction. knowledge, skills, and active learning significantly impact satisfaction, with active learning having the strongest effect. Additionally, knowledge has a significant positive effect on skills, and behavioral engagement has a significant positive effect on active learning. Conclusions: We recommend that teachers and academic administrators provide evaluations to enhance the Satisfaction of associate degree students.